ДО ПИТАННЯ ПРАВОВІДНОСИН ІЗ ПЕНСІЙНОГО ЗАБЕЗПЕЧЕННЯ ДЕРЖАВНИХ СЛУЖБОВЦІВ - Moiseev, Y.O.; Uralova, Y.P. (V. Mamutov Institute of Economic and Legal Research of the National Academy of Sciences of Ukraine, 2010)
The paper examines legal relations in pension provision for public servants. The features of elements included in legal relations of pension provision for public servants are specified, and juridical facts which serve the grounds for granting a pension for length of service for public servants have been classified.